2019
DOI: 10.12788/jhm.3305
|View full text |Cite
|
Sign up to set email alerts
|

Secure Text Messaging in Healthcare: Latent Threats and Opportunities to Improve Patient Safety

Abstract: E3ipants about the shortcomings of text messaging and allows the facilitator to segue into the "dos and don'ts" of text messaging and when a phone call might be more appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Given the potential advantages and concerns surrounding secure messaging use described above, further research is needed on the impact of secure messaging on clinician efficiency, workflow, cognitive burden, and downstream effects for patient care and clinician wellness, as emphasized by the American Medical Informatics Association’s 25×5 campaign to reduce EHR burden [ 43 ]. In addition, no standardized guidelines exist for secure messaging use or deployment [ 16 ], and additional research is needed to understand the messaging policies (such as establishing etiquette and guidelines for appropriate use and best practices for education on these topics) and platform features (such as batched alerts, priority indicators, improved notification design, or generative artificial intelligence) that best enhance clinical care and minimize the potential negative effects of secure messaging use [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential advantages and concerns surrounding secure messaging use described above, further research is needed on the impact of secure messaging on clinician efficiency, workflow, cognitive burden, and downstream effects for patient care and clinician wellness, as emphasized by the American Medical Informatics Association’s 25×5 campaign to reduce EHR burden [ 43 ]. In addition, no standardized guidelines exist for secure messaging use or deployment [ 16 ], and additional research is needed to understand the messaging policies (such as establishing etiquette and guidelines for appropriate use and best practices for education on these topics) and platform features (such as batched alerts, priority indicators, improved notification design, or generative artificial intelligence) that best enhance clinical care and minimize the potential negative effects of secure messaging use [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a few studies have examined this topic, and they have similarly shown a marked increase in message volume and interruptions 10 and raised concerns regarding alarm fatigue and the potential for missing urgent messages. 15 These issues can have negative consequences for patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Another recent article identified more challenges, including alarm fatigue leading to delayed or incorrect responses, shift in communication away from critical face-to-face communication, and communication failures due to message errors. 15 These issues can have a detrimental effect on patient safety and clinical workflow. 16 The purpose of this study was to describe pediatric residents' and nurses' perspectives on STMS use and impact at a quaternary care children's hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many benefits of secure messaging [20,34], there are also several challenges to using chat for patient management communication. Risks include the development of alarm fatigue, the liability associated with critical communications, and communication errors that may occur [10]. Physical therapy departments would be wise to develop guidelines for the use of secure chat to safeguard patients against harm and reduce redundancy in communication.…”
Section: Evolving Physical Therapy Care Provisionmentioning
confidence: 99%